Pengaruh Digital Marketing, Harga, dan Diskon Terhadap Keputusan Pembelian Paket Internet dalam Aplikasi Axis di Kabupaten Magelang - Murtini, Mukti; Alim, Taqdirul; Nurlaila, Nindy Setya (Journal of Management Branding, 2025)
The development of digital marketing technology in the telecommunications sector has changed the way axis company interacts with customer. The purpose of this study is to determine the effect of digital marketing, prices, and discount on the decision to purchase internet packages in the Axisnet application in the Magelang Regency. The sample of this study is users or customers who use and buy internet packages in the Axisnet application. while the sampling method used is purposive sampling, namely Axisnet application users. Data collection in this study was carried out by distributing questionnaires to Axisnet application users. The number of respondents collects was 100 people. The data was then processed using SPSS 30 program. Based on the results of the research that has been done, it can be concluded that digital marketing, prices, and discounts have a simultaneous effect on the decision to purchase internet packages in the Axisnet application